Implications Of Intravascular Catheter In A Blood Vessel During Medical Treatment Using Computational Fluid Dynamics - Chong, Shin Yun (Universiti Sains Malaysia, 2021)
Intravascular (IV) catheters are a frequently used medical device in intravenous treatment, which is the administration of medications or fluids into a patient's veins. It is also one of the most frequently used invasive medical procedures. IV catheters frequently cause numerous relevant complications, which often result in patient discomfort. Most of the current research is based on experiment or randomised controlled trials involving both real-life patients and medical practitioners. The purpose of this project is to investigate the impact of different diameters of intravascular catheters and saline solution input velocities on the blood vein through Computational Fluid Dynamics (CFD) in ANSYS Fluent. The simulation is also verified against experimental data. From the results, the 22G catheter has the most steady and lowest maximum pressure among the five diameters, whereas the 18G and 22G catheters have the lowest maximum velocity in general. The inlet saline velocity of 0.7 m/s have a consistent decrease in maximum velocities with time compared to other velocities, while the inlet saline velocity of 0.3 m/s has the consistent lower maximum pressures. Overall, the 22G catheter with inlet saline velocity of 0.3 m/s can be chosen to be used in intravenous therapy for patients as it has lower risks of affecting the blood vein of patients.